Students’ Gambits and Debate Structure in National University Debating Championship (NUDC) 2018 of West Java - Permatasari Gunawan, Yayang Gita; Yuliasri, Issy; Fitriati, Sri Wuli (Universitas Negeri Semarang, 2019)
This study aimed to explain the appropriateness of using gambits in students’ debate competition, the debate structure realized in the students’ debate competition, the contribution of gambits to the students’ debate structure, and the ways the students overcome the difficulties of using gambits in the debate competition. To achieve the aims, this study used discourse analysis as the research design. To collect the data, this study used video recorder in observation and interview as the instrument. This study applied Keller and Warner (1988)’s theory about conversation gambits and Harvey-Smith (2011)’s theory about debate structure to analyze the data. The subjects in this study were 40 undergraduate students (20 teams) from different universities participating in National University Debating Championship (NUDC) 2018 of West Java. Their debate competition (five exhibitions) were observed, transcribed and analyzed. The objects of the study were the students’ gambits and debate structure. The findings from observation showed that most of debaters used variety of gambits from opening, linking and responding gambits to deliver their speech appropriately. Most of debaters applied the debate structure in the debate competition. Only one or two debater/s did not apply some parts of the debate structure. The use of gambits gave high contribution to the students’ debate structure to support them in making introduction, rebuttals, arguments, and conclusion in their debate speech. The results of interview showed that most of students learned gambits naturally and to overcome the difficulties of using gambits in any situation was by learning and practicing hard to make the speech perfect.